Análise das políticas de assistência estudantil: pensando as formas de permanência de estudantes universitários no contexto da governamentalidade neoliberal - Lima, Maria Janete de (2022)
This thesis studies the neoliberal governmentality of Student Assistance Policies at the Public University, through two Student Assistance programs that act in the face of access, permanence and training, which are: the University Residence and the Undergraduate Teaching Assistance Program (PAEG), both from the Teacher Training Center (CFP), at the Federal University of Campina Grande (UFCG). With regard to the research's guiding questions, do I seek to understand student assistance policies in undergraduate courses and neoliberal governmentality in contemporary Brazil regarding permanence in university education? How have student assistance policies promoted the qualified permanence of students in the CFP beyond neoliberal governmentality? Its general objective is to analyze student assistance programs as policies of neoliberal governmentality and the construction of the qualified permanence of students in university education, considering the discourses of “assistance” and “permanence”; and as specific objectives: a) Understand the mechanisms of access and permanence of students in the University Residence and PAEG programs at CFP, contextualizing the exercise of biopower; b) Knowing the actions carried out in the programs, considering the permanence of students in the CFP/UFCG from the students' point of view and their relationship with training; c) Understand the vision of beneficiary students on student assistance policies, regarding the exercise of biopolitics and biopower; d) Identify the mechanisms for keeping students in relation to the control practices developed by the institution. The theoretical foundation focuses on the concepts of neoliberal governmentality, biopolitics and biopower to understand the object of study in an articulation between the authors' thinking, in the context of social policies of student assistance, as public policies. The theoretical-methodological perspective of the analysis of the research data was carried out through the analysis of the Foucaultian discourse, having as basic categories: the subject, the utterance, the device and the discourse. As a data collection technique, we have semi-structured interviews with students from the PAEG, the University Residence, the techniques of the Student Support Coordination-CAE and the representative of the Pro-Rectory of Community Affairs-PRAC/UFCG, as well as using document analysis. When students remain in assistance policies, we can observe the predominance of Brazilian neoliberal governmentality, which is remade every day, restructured through speeches and actions, thus creating the rhetoric of control that builds the Brazilian social reality; also observing the forms of resistance, whether from students, or from class bodies such as FONAPRACE, ANDIFES and managers committed to Student Assistance. The micropowers and micro devices of governmentality are presented in the discourses during the research, both by the students and by the management; considering discourses as pressing in social relations and as a language formed by crossing. In a unique way for the students, the discourses are constructed in the sense of establishing power-knowledge relationships as possibilities for the transformation of these subjects through student assistance policies.